A simulation study on the climatic responses to short-lived climate pollutants changes from the pre-industrial era to the present - Xie, B.; Zhang, H. (Frontiers in Earth Science, 2022)
Short-lived climate pollutants (SLCPs) including methane, tropospheric ozone, and black carbon in this work, is a set of compounds with shorter lifetimes than carbon dioxide (CO2) and can cause warming effect on climate. Here, the effective radiative forcing (ERF) is estimated by using an online aerosol–climate model (BCC_AGCM2.0_CUACE/Aero); then the climate responses to SLCPs concentration changes from the pre-industrial era to the present (1850–2010) are estimated. The global annual mean ERF of SLCPs was estimated to be 0.99 [0.79–1.20] W m−2, and led to warming effects over most parts of the globe, with the warming center (about 1.0 K increase) being located in the mid-high latitudes of the Northern Hemisphere (NH) and the ocean around Antarctica. The changes in annual mean surface air temperature (SAT) caused by SLCPs changes were more prominent in the NH [0.78 (0.62–0.94) K] than in the Southern Hemisphere [0.62 (0.45–0.74) K], and the global annual mean value is 0.70 K. By looking at other variable responses, we found that precipitation had been increased by about 0.10 mm d−1 in mid- and high-latitudes and decreased by about 0.20 mm d−1 in subtropical regions, with the global annual mean value of 0.02 mm d−1. Changes in SLCPs also influenced atmospheric circulation change, a northward shift in the Intertropical Convergence Zone was induced due to the interhemispheric asymmetry in SAT. However, it is found in this work that SLCPs changes had little effect on global average cloud cover, whereas the local cloud cover changes could not be ignored, low cloud cover increase by about 2.5% over high latitudes in the NH and the ribbon area near 60°S, and high cloud cover increased by more than 2.0% over northern Africa and the Indian Ocean. Finally, we compared the ERFs and global and regional warming effects of SLCPs with those induced by CO2 changes. From 1850 to the present, the ERF of SLCPs was equivalent to 66%, 83%, and 50% of that of CO2 in global, NH, and SH mean, respectively. The increases in SAT caused by SLCPs were 43% and 55% of those by CO2 over the globe and China, respectively.